Comunalización jesuita y desintegración reduccional. Políticas alternativas de colonización en la frontera luso-española - Quarlery, Lía (2014)
The present work, through a broad historical survey and an analysis of laws on mission administration during the period of domination by the Society of Jesus (1620-1767) and the post-Jesuit period (1768-1801) in the territory occupied by the Guaraní, analyzes the characteristics of two models of organization and administration for the Guaraní population: Jesuit communalism and Bourbon assimilation. Specifically, we reconstruct the ideological bases, the contextual factors and the political objectives inscribed in each model, as well as contrasting them via specific oppositional frames: purity and mestizaje, community and individual, spatial subjection and mobility, and segregation and assimilation.